2022
DOI: 10.3390/cells11152350
|View full text |Cite
|
Sign up to set email alerts
|

Immunorthodontics: PD-L1, a Novel Immunomodulator in Cementoblasts, Is Regulated by HIF-1α under Hypoxia

Abstract: Recent studies have revealed that hypoxia alters the PD-L1 expression in periodontal cells. HIF-1α is a key regulator for PD-L1. As hypoxia presents a hallmark of an orthodontically induced microenvironment, hypoxic stimulation of PD-L1 expression may play vital roles in immunorthodontics and orthodontically induced inflammatory root resorption (OIIRR). This study aims to investigate the hypoxic regulation of PD-L1 in cementoblasts, and its interaction with hypoxia-induced HIF-1α expression. The cementoblast (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been reported by some previous researchers that HIF-1α plays an important role in triggering the glycolysis of tumor cells and enhancing their 18 F-FDG uptake [ 35 , 36 , 37 ]. In addition, HIF-1α could upregulate PD-L1 expression by binding directly to the hypoxia-responsive element (HRE) in the PD-L1 promoter [ 38 , 39 , 40 ]. According to these findings, the positive correlation between PD-L1 expression and 18 F-FDG accumulation could be mostly resulting from the activation of HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported by some previous researchers that HIF-1α plays an important role in triggering the glycolysis of tumor cells and enhancing their 18 F-FDG uptake [ 35 , 36 , 37 ]. In addition, HIF-1α could upregulate PD-L1 expression by binding directly to the hypoxia-responsive element (HRE) in the PD-L1 promoter [ 38 , 39 , 40 ]. According to these findings, the positive correlation between PD-L1 expression and 18 F-FDG accumulation could be mostly resulting from the activation of HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The growth medium was replaced every day with fresh medium. Until grown of adherently cementoblasts to 80% confluency, the concentration of FBS was set to 0.5% as a starvation medium 14 h prior to CNTF stimulation [ 30 ]. All experiments were performed using cells at the 2nd to 5th passages.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated to be up-regulated upon immune activation conditions, such as inflammations [ 83 ]. In recent studies, we identified for the first time that PD-L1 is induced and constantly expressed on murine cementoblasts in response to compression and hypoxia, simulating orthodontic-force-induced microenvironmental changes [ 84 , 85 ]. In detail, the recent data revealed that the application of a compressive force at a magnitude of 2.4 gf/cm 2 enhances the PD-L1 expression in cementoblasts.…”
Section: Pd-l1 and Oiirrmentioning
confidence: 99%
“…In addition, it was revealed that HIF-1α plays an pivotal role in the PD-L1 modulation [ 84 ]. Another very recent study conducted by our group showed that long-term exposure to hypoxic conditions augmented PD-L1 expression on cementoblasts [ 85 ]. Based on these observations, it is reasonable to hypothesize that this ligand could serve as a potential target for therapies aimed at anti-OIIRR [ 86 ] ( Figure 3 ).…”
Section: Pd-l1 and Oiirrmentioning
confidence: 99%